2013
DOI: 10.1111/cas.12127
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection increases subsequent urinary tract cancer risk: A population‐based cohort study

Abstract: This study examines the possible association between urinary tract infection (UTI) and urinary tract cancer (UTC). Data from the National Health Insurance system of Taiwan were used for the analysis. The UTI cohort included 70 116 patients who were diagnosed and recruited between 1997 and 2010. Each patient was randomly frequency-matched with two people without UTI from the general population based on their age, sex, and month of UTI diagnosis. Cox's proportional hazard regression analysis was used to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Our research group recently conducted a cohort study using NHIRD to evaluate the relationship between urinary tract infection and subsequent urinary tract cancer risk. Our positive findings encouraged us to conduct a study with a similar design to determine whether tonsillectomy relates to the risk of developing cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Our research group recently conducted a cohort study using NHIRD to evaluate the relationship between urinary tract infection and subsequent urinary tract cancer risk. Our positive findings encouraged us to conduct a study with a similar design to determine whether tonsillectomy relates to the risk of developing cancer.…”
Section: Discussionmentioning
confidence: 96%
“…A study by Fan et al in 2017 had also identified an association between prostate cancer and bacteriuria [40]. Another study by Sun et al in 2013 had also confirmed the association among urinary tract cancers and asymptomatic bacteriuria [8]. is difference might be due to the variation in study design and characteristics of the study population.…”
Section: Discussionmentioning
confidence: 97%
“…Bacteriuria is the presence of microbial pathogens in the urethra, bladder, ureter, and pelvis of the kidney [5,6]. Escherichia coli, Klebsiella pneumonia, Proteus mirabilis, Pseudomonas aeruginosa, Staphylococcus saprophyticus, Enterococcus faecalis, and Streptococcus agalactiae are the leading cause of urinary tract infections [7,8]. Obstruction of the urinary tract, use of a catheter, immunocompromised condition, estrogen deficiency, genetic predisposition, and sexual intercourse are common risk factors for urinary tract infection [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies, most from the second half of the twentieth century and conducted in small populations, have investigated the association between episodes of (lower) UTI and the risk of urinary bladder cancer (UBC). The majority of these studies report increased UBC risks for any vs no UTI, in both men and women ( Wynder et al , 1963 ; Dunham et al , 1968 ; Howe et al , 1980 ; Kantor et al , 1984 ; Claude et al , 1986 ; La Vecchia et al , 1991 ; Kunze et al , 1992 ; Sturgeon et al , 1994 ; Jhamb et al 2007 ; Sun et al , 2013 ), whereas some do not support a positive association ( Piper et al , 1986 ; Kjaer et al , 1989 ; González et al , 1991 ; Jiang et al , 2009 ). A few studies specifically address the number of UTI episodes or the duration between UTI and UBC diagnosis, the latter to prevent potential misclassification.…”
mentioning
confidence: 99%